Correlation of Mothers with History of Diabetes Mellitus and Infants with Anti-GAD65 - Salamy, Nanda Fadhilah Witris; Sari, Gadis Meinar; Purwanto, Bambang; Sulistiawati, Sulistiawati (Folia Medica Indonesiana, 2019)
The aim of this study was to analyze human sperm motility, viability, and morphology before and after cryopreservation. This true laboratory experimental study had pre and post randomized one group design. The study was conducted at the Embryology, Andrology, and Genetics Laboratory, Department of Medical Biology, Faculty of Medicine, Universitas Airlangga from August to November 2017. The eighteen samples of fresh semen were collected from male volunteers who agreed and signed the informed consent of the study. Samples were analyzed their motility, viability, and morphology before and after cryopreservation. Results of this study indicated differentiation between motility before and after cryopreservation. Cryopreservation process decreased progressive motility (42.22 + 9.46%; 17.83 + 6.24%; p< 0.0001) and increased the number of immotile spermatozoa (35.44 + 10.15%; 60.11 + 12.53%; p< 0.0001). Cryopreservation also decreased human sperm viability (73.78 + 8.91%; 40.83 + 12.89%; p< 0.0001) and morphology (10.94 + 4.96%; 7.39 + 3.90%; p< 0.0001). Cryopreservation of human spermatozoa caused the decreased of motility, viability, and morphology.